THE MATERIAL LAW PROTECTION OF WILD ANIMALS (The Pretoria Student Law Review, 2021)
The aim of this article is to consider the protection of wild animals and other living natural resources in South Africa from a material law perspective. To ensure completeness both the procedural law and problems with enforcement will be briefly considered. Possible improvements and solutions to difficulties will also be submitted. This article will focus mostly on the pre-1994 conservation ordinances which still apply in the nine new provinces. Wild animals are protected in these provincial laws on a species based approach where animals are listed in categories and each category is provided with a different degree of protection. These ordinances are the main source of law which deal with the conservation, protection and exploitation of wild animals, indigenous plants and freshwater fish in South Africa and is usually referred to as ‘wildlife law.’
Keywords: protection of wild animals; living natural resources; South Africa; material law; procedural law; ‘wildlife law’